Simulation of fuzzy logic for watering plant using sprinkler - Nurul Idayu, Mohamad (2012)
Project of simulation of fuzzy logic for watering plant using sprinkler is about simulate the total water that sprinkler needs to spray to the plants based on the inputs of the project. The inputs of the project are weather temperature and soil moisture temperature.This project is developed because to help the farmers to control the total of water for watering their plants. This system is suitable for users who use the sprinkler to watering their plants like farmers.The project actually created for Kuantan Department of Agriculture,Pahang to help them to control the total water of watering the plant.The system can use when user inserts the value of input;weather temperature and soil moisture temperature. After that,the total of water that watering plant will be calculated when the user clicks the calculate button. Then,user needs to click's simulation button to see the simulation of this project. From the system,hopefully can help the farmers and the other user to use this system to control their total of water of watering plant.